Service Quality and Workplace Conditions as Determinants of Civil Servant Satisfaction: A Study from Central Papua Province - Amawi Mose Arens Bonai; Natalia Paranoan; Sita Yubelina Sabandar (Management Study Program, Universitas Kristen Indonesia Paulus, 2025)
This study investigates the impact of service quality and work environment on employee satisfaction at the Regional Agency for National Unity and Politics in Central Papua Province, Indonesia. Utilizing a quantitative approach, data were collected from 40 civil servants through structured questionnaires. The results were analyzed using multiple linear regression. The findings indicate that both service quality and work environment significantly influence employee satisfaction, with work environment emerging as the more dominant factor. This highlights the critical role of creating a conducive and supportive workplace in enhancing job satisfaction within public institutions. The implications of this research suggest that regional government bodies aiming to improve employee satisfaction should prioritize internal service quality while ensuring a positive work environment. This study contributes to the literature on public sector human resource management by providing empirical evidence from a newly established autonomous region in Indonesia. Limitations and directions for future research are also discussed.